„Minden elvégeztetett!”: Médeia és Iasón Pier Paolo Pasolini filmjében - Csantavéri, Júlia (Studia Litteraria, 2017)
The present study examines how Pasolini’s film on Medea’s devouring passion fits in the poet-director’s general discourse conducted since the early ‘60s about the tragic lack of communication between the sacred past and the profane present, and how it links to its direct antecedent Euripides’ play. It starts from the anthropological theory of Ernesto De Martino, and the concept of “presence” elaborated by him, which was well known and appreciated by Pasolini. In extending the story narrated by Euripides and focusing on the events of stealing the Golden Fleece as much as on Medea’s terrible vengeance, the director gains territory to enforce the anthropological point of view. Highlighting the link between Medea and the God of Sun reveals the cosmic perspective of the myth. The study analyses the relationships between the main characters and the way Pasolini uses and rewrites Euripides’ text with some shifts of emphasis, converting Medea’s story into a metaphor of a deep change in the western world called anthropological genocide by Pasolini.